Effects of uric acid-lowering therapy (ULT) on renal outcomes in CKD patients with asymptomatic hyperuricemia: a systematic review and meta-analysis - Yuxin Luo; Qirong Song; Jiaxiao Li; Sha Fu; Wenjuan Yu; Xiaofei Shao; Jinxiang Li; Yuliang Huang; Junzhe Chen; Ying Tang (BMC Nephrology, 2024)
Abstract Background It is well known that asymptomatic hyperuricemia and gout play an important role in patients with chronic kidney disease (CKD). However, the effect of uric acid-lowering therapy (ULT) on the prognosis of CKD patients with asymptomatic hyperuricemia remains controversial. Therefore, we aim to investigate the influence of ULT on renal outcomes in these patients. Methods Comprehensive searches were conducted in PubMed, EMBASE, China National Knowledge Internet (CNKI), and the Cochrane Library, up until January 2024. We included randomized controlled trials (RCTs) that evaluated the effects of ULT on renal outcomes in CKD patients with asymptomatic hyperuricemia. Results A total of 17 studies were included in the meta-analysis. Compared with placebo or no treatment, ULT preserved the loss of estimated glomerular filtrating rate (eGFR) (Weighted mean difference [WMD] and its 95% confidence intercal(CI): 2.07 [0.15,3.98] mL/min/1.73m2) at long-term subgroup. At the same time, short-term subgroup also proved the preserved loss of eGFR (WMD 5.74[2.09, 9.39] mL/min/1.73m2). Compared with placebo or no treatment, ULT also reduced the increase in serum creatinine (Scr) at short-term (WMD -44.48[-84.03,-4.92]μmol/L) subgroup and long-term (WMD -46.13[-65.64,-26.62]μmol/L) subgroup. ULT was associated with lower incidence of the events of doubling of Scr without dialysis (relative risk (RR) 0.32 [0.21, 0.49], p < 0.001). However, no difference was found for lower incidence of acute kidney injury (AKI) (p = 0.943). Conclusions According to our study, ULT is beneficial for slowing CKD progression both in short to long-term follow-ups. Additionally, in patients younger than 60 years old, the protective effect of ULT on renal outcome is more pronounced. However, it showed no significant difference in the incidence of AKI. These findings underscore the importance of considering ULT in clinical strategies for CKD patients with asymptomatic hyperuricemia.